Clinico-histopathological and ultrasonographic correlation of abnormal uterine bleeding in perimenopausal and postmenopausal women - ., Sharanya; Thomas, Julie (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Abnormal uterine bleeding (AUB) accounts for one of the most common gynaecological problem, almost one third of total cases. The study was a prospective study done from December 2017 to November 2019. The histopathological reports of endometrial pattern as well as that of hysterectomy specimens were correlated with clinical diagnosis and ultrasonographic findings. The main objective was to study the correlation between clinical, ultrasonographic and histopathological correlation of AUB in perimenopausal, menopausal and postmenopausal women. Methods: Formal Permission was obtained from the administrator of St. Philomena’s hospital. Ethical clearance was obtained from institutional ethical review board of St. Philomena’s hospital. Informed consent was obtained from observational group and confidentiality was assured. Data entry and analyses was done using the Statistical Package for Social Sciences (SPSS) for Windows software (version 20.0; SPSS Inc, Chicago). Results: A total number of 165 cases were studied. Maximum women were in the age group of 40-55 years 87.27%. Most common presentation of abnormal uterine bleeding is menorrhagia which accounts for 72.7% of women (120 women). The most common finding noted in USG was fibroid uterus which accounts for 44.2% of women (73 women). Most commonly observed histological pattern noted were proliferative (62.4%) followed by secretory endometrium (8.5%) and simple endometrial hyperplasia with atypia (8.5%). Conclusions: In conclusion, AUB is one of the most common condition for which patients seek advice in the gynaecological outpatient department. Analysis of histopathology of endometrium in abnormal uterine bleeding helps in management of patients and to know the pathological incidence of structural causes in AUB prior to surgery.